Ženski liki sodobnih slovenskih pisateljic v izbranih zgodovinskih romanih - Šela, Ana (Studia Historica Slovenica, 2018)
This article deals with contemporary Slovenian female writers of historical fction. In the main part is presented the analysis of selected contemporary historical novels by Mojca Kumerdej (Kronosova žetev, 2016), Zlatka Rakovec-Felser (Vražja Liza, 2017), and Zlata Vokač (Knjiga senc, 1993), published after the year 1991 and set in the literary periods of the 15th, 16th and early 17th century. During said periods, the Slovenian ethnic territory was marked primarily with the collapse of the Counts of Celje, Turkish invasions, reformation and counter-reformation. The women who sought a life in business or otherwise wanted to become successful in their careers were quickly silenced. Also briefy presented in the article are the development of the Slovenian historical novel and the role of Slovenian female authors in the development of said novels.
Keywords: literarni liki; slovenska književnost; slovenske pisateljice; zgodovinski romani; ženska književnost